The Role of Scientific Research in Economic Development - Khasankhonova Nodira Isametdinovna (International Journal on Economics, Finance and Sustainable Development, 2022)
In the article is considered the real state of products’ science-intensiveness in the country. In particular, the category of science intensity of products, its main constituent factors such as research, development, inventions, R&D costs, innovative products are discussed. In the article analyzed the Decree of the President of the Republic of Uzbekistan dated April 1, 2021 No. DP-5047 "On measures to further improve state policy in the field of science and public administration in the field of innovative development", its effectiveness in science-intensive products.